Revision of the genus Haplomesus (Isopoda: Asellota: Ischnomesidae) with erection of four new genera - Kavanagh, F.A.; Wilson, G.D.F. (Invertebrate Systematics, 2007)
This paper presents a revision of Haplomesus Richardson, 1908 (Ischnomesidae). Poor character definition, ineffective diagnosis of the genus and inadequate or poor descriptions and illustrations have resulted in difficulties in identification of species and generic membership. This study is based on type material and descriptions in the literature and encompasses 28 species. Four new genera are created, justified by a phylogenetic analysis of 37 ingroup taxa and two outgroup taxa. Three species of the ingroup were excluded owing to missing data. Four species are retained in Haplomesus sensu stricto, two species are removed to Cornuamesus, gen. nov., 11 species are removed to Fortimesus, gen. nov. and 12 species are removed to Gracilimesus, gen. nov. One species, Haplomesus franklinae Merrin & Poore, 2003 is removed from the group and placed in Contrarimesus, gen. nov. with another species, Ischnomesus curtispinis Brandt, 1992. The species level is conferred on Haplomesus insignis orientalis Birstein, 1960. Haplomesus quadrispinosus sensu Brandt (1992) is removed from H. quadrispinosus (Sars, 1879) and Haplomesus ?gorbunovi sensu Svavarsson (1984) is removed from Gracilimesus gorbunovi (Gurjanova, 1946).